Investigation of Thiocarbamates as Potential Inhibitors of the SARS-CoV-2 Mpro - Katarzyna Papaj; Patrycja Spychalska; Katarzyna Hopko; Patryk Kapica; Andre Fisher; Markus A. Lill; Weronika Bagrowska; Jakub Nowak; Katarzyna Szleper; Martin Smieško; Anna Kasprzycka; Artur Góra (MDPI AG, 2021)
In the present study we tested, using the microscale thermophoresis technique, a small library of thionocarbamates, thiolocarbamates, sulfide and disulfide as potential lead compounds for SARS-CoV-2 Mpro drug design. The successfully identified binder is a representative of the thionocarbamates group with a high potential for future modifications aiming for higher affinity and solubility. The experimental analysis was extended by computational studies that show insufficient accuracy of the simplest and widely applied approaches and underline the necessity of applying more advanced methods to properly evaluate the affinity of potential SARS-CoV-2 Mpro binders.